Effects of Ozone Wash for Inactivation of S. Typhimurium and Background Microbiota on Lettuce and Parsley. Issue 3 (24th June 2013) - Sengun, Ilkin Yucel
<x xml:space="preserve">Abstract</x> Abstract Experiments were done with ozonated water to evaluate its efficacy in reducing the numbers of Salmonella Typhimurium and total mesophilic aerobic bacteria (TMAB) on vegetables and in improving their storage quality. Ozonated water (0.5, 1.0 and 1.5 ppm) treatment for 3, 5 and 10 min caused reductions in the number of TMAB of lettuce and parsley samples ranging between 0.48–1.25 and 0.40–1.03 log units, respectively. The counts of S. Typhimurium on inoculated lettuce samples were reduced by ozonated water in the range of 1.14–3.06 log units reductions, while 0.28–2.57 log units reductions were achieved for parsley samples. On the other hand, the effect of tap water in reducing TMAB and S. Typhimurium counts was found ranging between 0.10–1.20 and 0.44–0.60 log units, respectively. Reduction capacity of ozonated water (1.5 ppm/5 min) on microbial population was also tested in a school kitchen and results were similar with the laboratory findings (P > 0.05). To determine the effects of ozonated water on the storage quality of the samples, TMAB and mold‐yeast counts of vegetables were investigated during the storage period at 4C for 15 days. Results of the study showed that ozonated water is mainly useful for reducing S. Typhimurium cells from vegetables. Practical Applications Conventional ozone generators, which needs compressors, air dryers, oxygen concentrators and ozone injectors, are too bulky to be used, in point‐of‐installations. On the other hand, in ozo‐pen system, technology developed in recent years, ozone can be produced directly from the water to be treated itself instead of producing ozone from a dry air or dry oxygen gas source, and the system only needs handheld ozone generator, portable container and water. This study showed that ozonated water, which can be produced practically by ozone probes in a small scale and also at household levels, is a good alternative for improving microbiological quality of fresh produce.